Sistem Pemerintahan Adat Tigo Luhah Semurup Kabupaten Kerinci pada Tahun 1979 – 2019 - Febriensa, Refolta; Erniwati, Erniwati (Jurusan Sejarah FIS UNP, 2025)
The background of this study is the change in the customary government system in the Tigo Luhah Semurup area, Kerinci Regency, as an impact of the implementation of Law No. 5 of 1979. The law abolished the existence of customary government and replaced it with a village government system. This change gave rise to dualism of power between customary institutions and village governments, and raised concerns about the erosion of local cultural identity. The purpose of this study is to examine the process of transformation of the customary government system to village government, the institutional role of customary post-transformation, and how the community adapts customary values ​​in the modern government structure. This study uses a qualitative approach with historical methods as explained by Sjamsudin and Kartodirjo, which includes the stages of heuristics, source criticism, interpretation, and historiography. The results of the study show that although administratively the Kemendapoan system was abolished, customary values ​​and practices persisted through the process of cultural adaptation and symbolic resistance. Changes occurred gradually through the influence of the dominant state on the government system in Tigo Luhah Semurup. However, the community still maintains customary institutions as a source of social legitimacy. In conclusion, the transformation of the government system does not completely eliminate the role of custom, but creates a new space for negotiation between tradition and modernity.